RATE OF NEUROLOGICAL RECOVERY IN TRAUMATIC SPINAL CORD INJURIES AFTER SURGICAL INTERVENTION - Razaq, Mohammad Naeem Ur; Ali, Bahadar; Khan, Muhammad Zahid; Waqar, Muhammad; Satar, Abdul; Khan, Muhammad Arif (Journal of Ayub Medical College Abbottabad, 2017)
Background: Spinal injuries are the most devastating injuries and affect every aspect of patients’ lives. This may cause lifelong disability due to spinal cord injury. Recovery of neurological functions is highly desirable. Early or late surgical intervention is still debatable, but majority recommend early intervention. The result of late surgical intervention in term of neurological recovery is not clear. This study focuses on neurological recovery after late surgical intervention. The objective of this study was to assess neurological recovery in term of ASIA grading in patients with traumatic spinal cord injury. Methods: This descriptive cross-sectional study was performed from June 2013 to June 2016. All patients treated for spinal trauma with spinal cord injury, operated after 24 hrs of injury were included in the study. Neurology was assessed according to ASIA scale preoperative and at 6 months. Data was analysed with the help of SPSS. Results: Total of 149 patients, 32 (21.5%) were female and 117 (78.5%) male were included. mean age was 32±13.11 years. Ninety-six (64.4%) patients presented with fall while 53 (35.6%) presented with motor vehicular accidents (MVA). according to AO comprehensive classification 76 (51.1%) patients were type C, 47 (31.5) were type B and 26 (17.4%) were type A. preoperative neurology was ASIA A 65 (43.6%), B12 (8.1%), C 59 (39.6%) and D 13 (8.7%). Mean delay in surgery was 3.6±1.8 days with minimum of 1 and maximum 14 days. ASIA grading on 6 months was ASIA A 61 (40.9%), B4 (2.7%), C 26 (17.4%), D 33 (22.1%) and E 25 (16.8%). the overall improvement in neurology was in 67 (45%) of patients. improvement by one grade was documented in 49 (32.9%) patients, by two grades in 17 (11.4%) and by three grades in one patient (.7%). Conclusion: fall from height is a major cause of spine injuries in our set up followed by RTA. Preventive measures need to be instituted to lessen the devastating outcome. Keywords: Spinal injuries; Spinal cord injury; ASIA scale; Decompression